The Remaking of the Catholic Working Class: Detroit, 1919–1945 - Pehl, Matthew (Religion and American culture, 2009)
This essay examines the response of Catholics—both the institutional church and blue-collar laity—to the turmoil of the late 1930s and the rise of the United Automobile Workers in Detroit. It critiques an influential line of scholarship that holds that the ethnic working class was effectively secularized by the rise of mass culture, the welfare state, and industrial unions. Instead, the essay argues that religion—like class, gender, or race/ethnicity—might fruitfully be analyzed as a “consciousness” and, as such, remains fluid, malleable, and protean in the face of historical change. During the Depression years, blue-collar Catholics (especially Catholic men) experienced a re-creation of their religious consciousness to conform to the new world of industrial unionism. While Detroit’s “labor priests” established the Archdiocesan Labor Institute (ALI) and hosted labor schools in parishes across the city, lay people, spurred by the movement for “Catholic Action,” founded the Association of Catholic Trade Unionists (ACTU) to strengthen working-class faith and “Christianize the UAW.” More important, the ALI and ACTU collectively provided a new religious template within which working-class Catholics might reconcile—even intertwine—their class, gender, and religious identities. While the changes of the 1930s did assimilate ethnic Catholics more fully into the secular sphere, this essay demonstrates that such a process did not result in a “decline” in religious significance for many Catholic workers; more precisely, it meant a “re-making” of religious consciousness.